DEVELOPMENT OF INTERACTIVE E-BOOK TEACHING MATERIALS BASED ON LOCAL WISDOM USING WORDWALL EDUCATIONAL GAMES - Mahfiroh, Diyah; Muslim, Aji Heru (Institut of Shanti Bhuana, 2023)
This research is based on an analysis of teaching materials that do not contain local wisdom values ​​and a lack of creativity to develop innovative teaching materials using technological developments in the learning process due to time and human resources constraints faced by teachers. This study aimed to assess the feasibility and practicality of using interactive e-book instructional resources that incorporate local knowledge, using wordwall educational games. This study's research and development methodology relates to utilizing the R&D development model with the ADDIE step, which includes five stages: Analyzing, Designing, Developing, Implementing, and Evaluating. The results of the eligibility validation of media experts yielded a score of 82.2%, which indicated